DEVELOPMENT OF A MATHEMATICAL MODEL AND ALGORITHM FOR EVALUATING RESEARCH ACTIVITY INDICATORS BASED ON ARTIFICIAL INTELLIGENCE - Abdullayev, Elmurod Zaylobidinovich (SCIENCE and SOCIETY, 2026)
This article addresses the development of a mathematical model and algorithm for evaluating research activity indicators based on artificial intelligence technologies. During the study, a system of parameters characterizing research activities was established, and their interrelationships were analyzed using mathematical modeling methods. The proposed model includes the stages of data collection, preprocessing, feature extraction, and classification. The use of machine learning algorithms enables the automated evaluation of research activity indicators and improves the objectivity of decision-making processes. Experimental results demonstrate the high accuracy and reliability of the developed model. The proposed approach can be effectively applied in intelligent information systems, expert systems, and decision support systems.